Marine engineering steel resistant to seawater corrosion and preparation method thereof

By adopting the chemical component design of low-carbon, low silicon, and chromium, and SI dehydration, ZR-RE composite deoxidation technology, the existing lack of lack of seawater corrosion steel in resistance to local corrosion has achieved efficient and economical seawater resistant to seawater. Corrosion effect.

CN117210766BActive Publication Date: 2025-01-28WUHAN UNIV OF SCI & TECH +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310971957.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-01-28
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

The existing low-strength steel and stainless steel alloys with low-alloy resistance to seawater corrosion are insufficient in terms of local corrosion resistance and are relatively high in cost.

Method used

The chemical design of low-carbon, low silicon, and chromium medium chromium does not contain valuable corrosive metal elements such as Ni and CU. Reduce the density of corrosive activity mixed objects.

Benefits of technology

It has significantly improved the corrosion resistance of the seawater, reduced the cost of material, and is suitable for steel for various marine environment, especially in the seawater media rich in chlorine -rich seawater medium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117210766B_ABST
    Figure CN117210766B_ABST
Patent Text Reader

Abstract

The present invention relates to an offshore steel resistant to seawater corrosion and a preparation method thereof. The offshore steel is composed of the following chemical components by mass percentage: C: 0.011-0.069%, Si: 0.11-0.29%, Cr: 1.51-1.99%, Nb: 0.02-0.05%, Zr: 0.01-0.02%, RE: 0.0034-0.02%, and the balance is Fe and inevitable impurities. The mass percentages of Zr element and RE element also simultaneously satisfy the formula: 0.01% < Zr + RE < 0.02%, and Zr / RE = 1-3. The offshore steel of the present invention adopts a low-carbon, low-silicon, medium-chromium inexpensive chemical composition design, completely does not contain precious corrosion-resistant metal elements such as Ni and Cu, and greatly reduces the material cost; does not adopt the traditional Al deoxidation technology, instead uses Si deoxidation, and is supplemented by Zr-RE composite deoxidation to form fine, dispersed and uniform composite oxysulfides, greatly reducing the density of corrosion-active inclusions and significantly improving the seawater corrosion resistance, and is suitable for steels used in marine environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a marine engineering steel resistant to seawater corrosion and a preparation method thereof. Background Art

[0002] The total area of ​​the ocean is about 70% of the total area of ​​the earth. There are many kinds of resources in the ocean. How to reasonably and efficiently develop and utilize marine resources has become a hot topic today. Research and development of seawater corrosion-resistant steel is an important basis for its sustainable development. The salt content in the ocean is about 3.5%, and Cl- is highly corrosive. Corrosion not only causes waste of steel materials, but more importantly, it causes unpredictable losses to marine structures and equipment. Therefore, how to improve the corrosion resistance of steel materials has become one of the key technologies for marine engineering steel.

[0003] Seawater corrosion-resistant steel is a type of low-alloy, high-strength steel developed for use in tidal power generation, seawater power generation, seawater temperature difference, offshore wind power, ocean waves and other power generation equipment, as well as coastal cross-sea bridges, seabed containers related to marine development, various large-scale marine components used for resource development, as well as shipbuilding steel, polar icebreaking and other fields.

[0004] Foreign research on seawater corrosion-resistant steel began in the 1930s. Since 1930, the United States and Japan have begun to research and develop new types of seawater corrosion-resistant application steels. By 1946, the United States had developed a new type of steel sheet pile for application steel in the marine splash zone, and conducted in-depth research on the Ni-Cu-P series of low-alloy high-strength steels. Until 1951, a breakthrough was made and a new type of high seawater corrosion-resistant steel, Mariner steel, was developed. The United States was the first to start research on seawater corrosion-resistant steel. In 1951, the Ni-Cu-P series Mariner steel was born. The steel contains 0.5% Ni, 0.5% Cu, and 0.1% P. It has good seawater corrosion resistance in the splash zone, which is 2-3 times that of ordinary carbon steel. However, the P content in this type of steel is high (0.08-0.15%), and steel plates with a thickness greater than 20 mm are not suitable for welding and cannot be used to weld marine structural steel.

[0005] On this basis, countries around the world have successively developed various series of seawater corrosion-resistant steels according to their own conditions. For example, Japan has developed the Mariloy (Cu-Cr-P, Cu-Cr-A1-P, Cu-Cr-Mo) series of seawater corrosion-resistant low-alloy high-strength steels with a P content of ≤0.03% in response to the high P content and poor welding performance of "Mariner" steel. The main reasons why the Mariloy series of steels have such good corrosion resistance are: ① The coexistence of chromium and silicon promotes the formation of a stable chromium-silicon passivation film during the corrosion process, and can also prevent the growth of bacteria in polluted seawater, thereby slowing down the corrosion of steel; ② Because silicon, chromium, and copper are enriched in the rust layer and directly act on the metal surface, the rust products close to the substrate become small and dense, which hinders the diffusion of dissolved oxygen in seawater to the steel surface and slows down the corrosion rate of steel. Japan has conducted research on how to improve the weldability of seawater corrosion-resistant steel while saving costs. It was found that replacing the alloy element Ni with Cr can greatly reduce production costs; adding other alloy elements to steel, such as aluminum, cobalt, niobium, titanium, etc., is conducive to improving corrosion resistance. At present, the low-alloy seawater corrosion-resistant steels produced abroad can be divided into Ni-Cu-P series, Cr-Nb series, Cr-Cu series, Cr-Al series, Cr-Cu-Si series, Cr-Cu-Al series, Cr-Cu-Mo series, Cr-Cu-P series and Cr-Al-Mo series according to their composition series.

[0006] my country has developed nearly 200 types of seawater corrosion resistant steel test grades, among which 10Cr2MoAlRE, 08PVRE, 09MnCuPTi, 10MnPNbRE, 10NiCuAs, 10CrMoAl, etc. have passed the identification. In addition to the above-mentioned low-alloy high-strength steel, there are also the following types of seawater corrosion resistant stainless steel: (1) Austenitic stainless steel, which has good corrosion resistance, but its yield strength is insufficient, the average yield strength is ≤300MPa, and the yield strength is 450MPa-700MPa under special circumstances; (2) Ferritic stainless steel, whose yield strength is less than 300MPa; (3) Duplex stainless steel, which is different from the first two types, has a higher yield strength, which can reach 700MPa; (4) Precipitation hardening stainless steel, which has the advantage of high strength, but the disadvantage is obvious, that is, its seawater corrosion resistance is insufficient. In view of this, the present invention provides a marine engineering steel resistant to seawater corrosion and a preparation method thereof. Summary of the invention

[0007] Aiming at the problems that the existing seawater corrosion-resistant low-alloy high-strength steel and stainless steel alloy have insufficient seawater corrosion resistance, especially insufficient local corrosion resistance, and high cost; the present invention provides a seawater corrosion-resistant marine engineering steel and a preparation method thereof.

[0008] To solve the above technical problems, the first object of the present invention is to provide an offshore steel resistant to seawater corrosion, which is composed of the following chemical components by mass percentage: C: 0.011-0.069%, Si: 0.11-0.29%, Cr: 1.51-1.99%, Nb: 0.02-0.05%, Zr: 0.01-0.02%, RE: 0.0034-0.02%, and the rest is Fe and inevitable impurities; the mass percentages of Zr element and RE element also simultaneously satisfy the formula: 0.01% < Zr + RE < 0.02%, and Zr / RE = 1-3.

[0009] Among them, the functions of each element in the offshore steel resistant to seawater corrosion of the present invention are as follows:

[0010] C element: The C element is one of the most basic elements added to steel. Its solid solution strengthening and precipitation strengthening can significantly affect the mechanical properties of steel, but C will significantly reduce the local corrosion performance of steel; at the same time, C is not conducive to the welding performance of steel. Generally, for steel with excellent welding performance, the carbon content must be strictly controlled. Therefore, the C content in the offshore steel of the present invention is 0.011-0.069%.

[0011] Si element: Si can inhibit the generation of acid in the rust layer and prevent Cl - from invading. In the inner rust layer, Si mainly exists in the spinel oxide in the form of divalent oxide. Higher Si is beneficial to refining α-FeOOOH in the rust layer, making the inner rust layer dense and thus hindering the invasion of Cl - . At the same time, the Si element is dissolved in ferrite and austenite to play a strengthening role, improving the mechanical properties of steel. At the same time, adding Si element to steel can improve the fluidity of molten steel. However, when the Si element in the matrix exceeds a certain range, it will promote the nucleation of grain boundary ferrite, inhibit the formation of acicular ferrite, and increase the percentage of M-A components in steel. Excessive Si is not conducive to the plasticity and toughness of steel, and also reduces the welding performance of steel. Considering the above factors, the silicon content in the offshore steel of the present invention is 0.11-0.29%.

[0012] Mn element: Mn is an important solid solution strengthening element. When the carbon content in steel is relatively low, appropriate addition of alloying element Mn can play a good solid solution strengthening role. Mn dissolved in ferrite can improve the mechanical properties of steel. However, Mn element and P element will cause banded structure in steel, and adding Mn element to steel will expand the γ phase region and reduce the critical cooling rate of steel, making it easy to obtain bainite structure. In addition, the corrosion resistance of low-alloy high-strength steel is inversely proportional to the Mn content, so the Mn content in steel should not be too high. In order to improve the seawater corrosion resistance of the present invention, Mn is not used for strengthening as much as possible, and Cr element is used instead.

[0013] Cr element: As the Cr content in steel increases, α-FeOOH can be effectively refined. When the Cr content in α-FeOOH exceeds 5%, it can prevent the entry of corrosive anions, such as Cl - , thereby improving the seawater corrosion resistance of the steel. At the same time, the enrichment of Cr in the rust layer increases the electrode potential of the matrix. Taking the above factors into consideration, the chromium element in the marine steel of the present invention is 1.51-1.99%.

[0014] Nb element: Nb is an important grain-refining element in steel. NbC precipitated by strain in the hot rolling process can hinder the recovery and recrystallization of deformed austenite, and precipitate fine dispersed carbonitride particles at low temperature to pin dislocations, significantly improving the strength and toughness of steel. Taking all the above factors into consideration, the niobium content in the marine steel of the present invention is 0.02-0.05%.

[0015] Zr element: Zirconium is a strong carbide-forming element, a strong deoxidizing element and a complex oxysulfide-forming element. Adding a small amount of zirconium has the functions of degassing, purification and grain refinement, which is beneficial to improving the low-temperature performance of marine steel, improving the stamping performance, and significantly improving the hardenability of steel when dissolved in austenite. Therefore, the zirconium content of the marine steel of the present invention is 0.01-0.02%.

[0016] Rare earth elements: The main functions of rare earth elements in the steel matrix are as follows: purifying molten steel, modifying inclusions and microalloying. Purifying molten steel: Rare earth elements have extremely strong chemical reactivity, so they are very easy to combine with sulfur and oxygen elements in molten steel to form high-melting point compounds, precipitate from molten steel, and purify molten steel. In addition, rare earth elements also have strong deoxidation ability, which is stronger than Mg, Al and Ti elements, and equal to Ca elements. Their desulfurization ability is also very strong, second only to Ca elements. Modified inclusions: Adding rare earth elements to steel can change the shape, size and distribution of inclusions formed in steel, and react with inclusions to change the type of inclusions. It replaces harmful inclusions in steel to improve the mechanical properties of the steel matrix and effectively improve the seawater corrosion resistance of steel. Rare earth elements have strong metallic properties and preferentially combine with sulfur elements to eliminate the formed MnS inclusions, and make the inclusions spheroidized and dispersed, effectively controlling the type, morphology and distribution of inclusions. Adding rare earth elements to steel can form fine spherical complexes, which are dispersed and evenly distributed in the steel matrix, changing the distribution state of long MnS inclusions along the grain boundaries. At the same time, the compound inclusions formed by rare earth and other elements have a high melting point and precipitate before the molten steel solidifies. The dislocation matching degree of the formed rare earth compounds is similar to that of their crystals. They are finely and evenly distributed in the molten steel as nucleation particles, reducing the supercooling of the molten steel solidification and crystallization, refining the steel structure, and reducing segregation. Microalloying: Adding rare earth elements to steel can play a role in solid solution strengthening. In addition, rare earth elements and hydrogen elements are combined to reduce the sensitivity to hydrogen-induced cracking. Taking the above factors into consideration, the rare earth content in the marine steel of the present invention is 0.0034-0.02%.

[0017] The beneficial effects of the present invention are:

[0018] (1) The marine engineering steel of the present invention adopts a low-carbon, low-silicon, medium-chromium cheap chemical composition design, and does not contain precious corrosion-resistant metal elements such as Ni and Cu, thereby greatly reducing the material cost; the traditional Al deoxidation technology is not adopted, but Si deoxidation is used instead, and Zr-RE composite deoxidation is used to form fine, dispersed and uniform composite oxysulfides, which greatly reduces the density of corrosion active inclusions and significantly improves the seawater corrosion resistance.

[0019] (2) The marine engineering steel of the present invention is particularly suitable for marine environment steel such as marine engineering steel, ship and vessel steel, offshore fixed wind power steel, offshore floating wind power steel, coastal cross-sea bridge steel, tower steel, and rail steel, and can significantly improve the corrosion resistance in seawater media rich in chloride ions.

[0020] It should be noted that in the above formula, Zr / RE=1-3, Zr and RE respectively represent their respective mass percentages, and the value substituted into the above formula is the value before the percentage sign. For example, if the mass percentage of Zr is 0.012% and the mass percentage of RE is 0.006%, then Zr / RE=0.012 / 0.006=2 is substituted into the above formula.

[0021] Based on the above technical solution, the present invention can also be improved as follows.

[0022] Furthermore, it is composed of the following chemical components in mass percentage: C: 0.029-0.068%, Si: 0.15-0.28%, Cr: 1.55-1.78%, Nb: 0.025-0.049%, Zr: 0.01-0.0117%, RE: 0.0039-0.0099%, and the rest is Fe and inevitable impurities.

[0023] Further, it is composed of the following chemical components in mass percentage: C: 0.04%, Si: 0.20%, Cr: 1.75%, Nb: 0.035%, Zr: 0.012%, RE: 0.006%, and the rest is Fe and inevitable impurities.

[0024] The beneficial effect of adopting the above further scheme is that the marine engineering steel having the above chemical composition measured in percentage by mass has better seawater corrosion resistance.

[0025] Furthermore, in other inevitable impurities, the mass percentage of S element satisfies: S≤0.0010%.

[0026] Furthermore, the RE element includes lanthanum and cerium, and the weight ratio of the lanthanum element to the cerium element is (70-90): (10-30).

[0027] Furthermore, the microstructure types of the marine engineering steel are acicular ferrite and polygonal grain boundary ferrite, and the quantity ratio of the polygonal grain boundary ferrite to the acicular ferrite is 4-8.

[0028] Furthermore, the density of corrosion active inclusions in the marine steel is less than or equal to 5 / mm 2 .

[0029] Furthermore, under the condition that the static electrode potential is equal to -300mV, the saturation current density of the offshore steel is less than or equal to 6.0mA; under the condition that the mass content of NaCl in the seawater solution is 3.5%, the corrosion rate of the offshore steel is less than or equal to 0.04 / mm·a.

[0030] The second object of the present invention is to provide a method for preparing marine engineering steel resistant to seawater corrosion, comprising the following steps:

[0031] 1) The molten steel is smelted and refined in sequence, vacuum treated, and then continuously cast into billets to obtain ingots;

[0032] 2) performing conventional heating and soaking treatment on the ingot to obtain a heat-treated ingot;

[0033] 3) The heat-treated ingot is continuously rolled, and the final rolling temperature is controlled to be 750-850° C., and after rolling, it is cooled to 410-550° C. by water pouring, and then naturally cooled to room temperature to obtain marine steel.

[0034] Furthermore, the smelting and refining method in step 1) is: using a converter or an electric arc furnace to make molten iron and / or scrap steel, adjusting the temperature and composition to obtain molten steel, wherein the temperature of the molten steel is adjusted to 1549-1679°C, and the free oxygen content in the molten steel is 119-389ppm; allowing the molten steel to enter a ladle, and then using micro-sub-bubble stirring for 3-10 minutes, pre-deoxidizing the molten steel in the ladle using Fe-Si alloy or Fe-Si-Mn alloy, and adjusting the free oxygen content in the molten steel to 19-99ppm; stirring for 4-6 minutes with micro-sub-bubbles, and performing final deoxidation with a composite additive; and then performing LF refining, VD refining, or RH refining on the final deoxidized molten steel.

[0035] The composite additive is added to the molten steel in the form of block alloy or cored wire, the particle size of the composite additive is 5-19 mm, the amount of the composite additive added is 0.59-3.9 kg per ton of molten steel, and the composite additive is a composition of zirconium, lanthanum and cerium, and the weight ratio of zirconium, lanthanum and cerium is 8:1.8:4.2. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The potentiodynamic polarization results of the marine engineering steel prepared in Example 1 of the present invention in a 3.5% NaCl solution;

[0037] Figure 2 The potentiodynamic polarization results of the comparative steel of the present invention in 3.5% NaCl solution are shown;

[0038] Figure 3 The AC impedance results of the marine steel prepared in Example 1 of the present invention in a 3.5% NaCl solution; wherein (a) is a Nyquist diagram, (b) and (c) are Bode diagrams, and (d) is an equivalent circuit diagram;

[0039] Figure 4 The AC impedance results of the comparative steel of the present invention in 3.5% NaCl solution; wherein (a) is a Nyquist diagram, (b) and (c) are Bode diagrams, and (d) is an equivalent circuit diagram;

[0040] Figure 5 The constant potential polarization result of the marine engineering steel prepared in Example 1 of the present invention measured in a chloride ion medium;

[0041] Figure 6 The constant potential polarization results of the comparative steel of the present invention measured in a chloride ion medium;

[0042] Figure 7 This is a micrograph of corrosion active inclusions in the comparative steel of the present invention;

[0043] Figure 8 This is a micrograph of corrosion active inclusions in the marine engineering steel prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0044] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0045] The composite additive described below is a composition of zirconium, lanthanum and cerium, and the weight ratio of zirconium, lanthanum and cerium is 8:4.4:1.1; the comparative steel Q345 is final deoxidized using conventional aluminum blocks, aluminum particles or aluminum wires to form coarse and clustered aluminum oxides and their composite oxides.

[0046] Example 1

[0047] The present embodiment relates to a marine engineering steel resistant to seawater corrosion, which is composed of the following chemical components by mass percentage: C 0.04%, Si 0.20%, Cr 1.75%, Nb 0.035%, Zr 0.012%, RE 0.006%, S 0.0008%, and the rest is Fe and unavoidable impurities. The RE includes lanthanum and cerium, and the weight ratio of the lanthanum element to the cerium element is 90:10.

[0048] The present embodiment relates to a method for preparing a marine engineering steel resistant to seawater corrosion, comprising the following steps:

[0049] 1) The molten steel is smelted and refined in sequence, vacuum treated, and then continuously cast into billets to obtain ingots;

[0050] The specific method of smelting and refining in step 1 is as follows: after steelmaking with molten iron in a converter, the temperature and composition of the molten steel are adjusted, the tapping temperature is adjusted to 1615° C., and the free oxygen content in the molten steel is 205 ppm; after the molten steel enters the ladle, it is stirred with micro-sub-bubbles for 7 minutes, and then pre-deoxidation is performed in the ladle with Fe-Si alloy or Fe-Si-Mn alloy, and the free oxygen content in the molten steel is adjusted to 60 ppm. After stirring with micro-sub-bubbles for 5 minutes, final deoxidation is performed with a composite additive; the composite additive is added to the molten steel in the form of a block alloy or a cored wire, and the particle size of the composite additive is 12 mm; the amount of the composite additive added is 1.9 kg per ton of molten steel, and then the molten steel is subjected to LF and RH refining according to conventional processes.

[0051] Among them, LF refining:

[0052] The viscosity of the refined slag is controlled at 1.525-1.938 Pa·s to improve the ability of the slag system to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.25≤R≤7.45, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.158, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag retention time is ≥14.35min, the refining cycle is ≥39.47min, and the soft blowing time is guaranteed to be>4.58min, thereby controlling the outgoing [O] content.

[0053] Among them, RH vacuum treatment:

[0054] The vacuum chamber pressure is pumped down to below 66.67 kPa and maintained for 12.13-14.45 min. The bottom blowing argon flow rate is 10.35-19.58 m 3 / h to achieve 4 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.37 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 10.28-29.19℃ above the liquidus.

[0055] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1542°C and the casting speed is 1.23 m / s.

[0056] 2) The ingot is subjected to conventional heating and soaking treatment at a temperature of 1190° C. for 3.4 hours to obtain a heat-treated ingot.

[0057] 3) The heat-treated ingot is continuously rolled, and the final rolling temperature is controlled to be 810° C. After rolling, it is cooled to 490° C. by water pouring, and then naturally cooled to room temperature to obtain marine engineering steel.

[0058] The specific rolling method in step 3) is: heating at 1190° C. for 3.4 hours; continuously rolling to form a product steel plate, and controlling the final rolling temperature to 810° C., cooling to 490° C. by water after rolling; and naturally cooling to room temperature for standby use.

[0059] The microstructure of the offshore steel plate obtained according to the above composition and preparation process is acicular ferrite and polygonal grain boundary ferrite, and the ratio of polygonal grain boundary ferrite to acicular ferrite is 6. The density of corrosion active inclusions in the offshore steel plate is 4 / mm 2 The saturation current density of the offshore steel plate at the static electrode potential (Е = -300mV) is 5.5mA. The corrosion rate of the offshore steel plate in the simulated seawater solution (3.5wt% NaCl solution) is 0.035 / mm·a.

[0060] Example 2

[0061] The present embodiment relates to a marine engineering steel resistant to seawater corrosion, which is composed of the following chemical components by mass percentage: C 0.068%, Si 0.28%, Cr 1.78%, Nb 0.049%, Zr 0.0117%, RE 0.0039%, S 0.0010%, and the rest is Fe and unavoidable impurities. The RE includes lanthanum and cerium, and the weight ratio of the lanthanum element to the cerium element is 80:20.

[0062] The present embodiment relates to a method for preparing a marine engineering steel resistant to seawater corrosion, comprising the following steps:

[0063] 1) The molten steel is smelted and refined in sequence, vacuum treated, and then continuously cast into billets to obtain ingots;

[0064] The smelting and refining method in step 1) is as follows: after steelmaking with molten iron in a converter, the temperature and composition of the molten steel are adjusted, the tapping temperature is adjusted to 1670°C, and the free oxygen content in the molten steel is 380ppm; after the molten steel enters the ladle, micro-sub-bubble stirring is performed for 9 minutes, and then Fe-Si alloy or Fe-Si-Mn alloy is used in the ladle for pre-deoxidation, and the free oxygen content in the molten steel is adjusted to 90ppm, and after micro-sub-bubble stirring for 6 minutes, a composite additive is used for final deoxidation; the composite additive is added to the molten steel in the form of block alloy or cored wire, and the particle size of the composite additive is 18mm; the amount of the composite additive added is 3.8kg per ton of molten steel, and then the molten steel is subjected to LF refining and RH refining according to conventional processes.

[0065] Among them, LF refining:

[0066] The viscosity of the refined slag is controlled at 1.535-1.931 Pa·s to improve the slag system's ability to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.22≤R≤7.48, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.157, and the sulfur distribution coefficient is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag retention time is ≥14.43min, the refining cycle is ≥39.51min, and the soft blowing time is guaranteed to be>4.59min, thereby controlling the outgoing [O] content.

[0067] Among them, RH vacuum treatment:

[0068] The vacuum chamber pressure is pumped down to below 66.57 kPa and maintained for 12.11-14.23 min. The bottom blowing argon flow rate is 10.31-19.59 m 3 / h to achieve 5 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.31 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 10.23-29.29℃ above the liquidus.

[0069] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1541°C and the casting speed is 1.21 m / s.

[0070] 2) The ingot is subjected to conventional heating and soaking treatment at a temperature of 1185° C. for 3.45 hours to obtain a heat-treated ingot.

[0071] 3) The heat-treated ingot is continuously rolled, and the final rolling temperature is controlled to be 840° C. After rolling, it is cooled to 540° C. by water pouring, and then naturally cooled to room temperature to obtain marine steel.

[0072] In step 3), the rolling method is as follows: heating the ingot at 1180°C for 3.5 hours; continuously rolling the ingot into a product steel plate, and controlling the final rolling temperature to 840°C, cooling the ingot to 540°C after rolling by pouring water; and naturally cooling the ingot to room temperature for standby use.

[0073] The structure type of the offshore steel plate obtained according to the above composition and preparation process is acicular ferrite + polygonal grain boundary ferrite, and the ratio of polygonal grain boundary ferrite to acicular ferrite is 5. The density of corrosion active inclusions in the steel plate is 4.2 pieces / mm 2The saturation current density of the steel plate at the static electrode potential (Е=-300mV) is 5.8mA. The corrosion rate of the steel plate in the simulated seawater solution (3.5% NaCl solution) is 0.033 / mm·a.

[0074] Example 3

[0075] The present embodiment relates to a marine engineering steel resistant to seawater corrosion, which is composed of the following chemical components by mass percentage: C 0.029%, Si 0.15%, Cr 1.55%, Nb 0.025%, Zr 0.01%, RE 0.0099%, S 0.0008%, and the rest is Fe and unavoidable impurities. The RE includes lanthanum and cerium, and the weight ratio of the lanthanum element to the cerium element is 70:30.

[0076] The present embodiment relates to a method for preparing a marine engineering steel resistant to seawater corrosion, comprising the following steps:

[0077] 1) The molten steel is smelted and refined in sequence, vacuum treated, and then continuously cast into billets to obtain ingots;

[0078] The smelting and refining method in step 1) is as follows: after steelmaking in molten iron using a converter, adjusting the temperature and composition of the molten steel, adjusting the tapping temperature to 1590°C, and the free oxygen content in the molten steel to 150ppm; after the molten steel enters the ladle, stirring with micro-sub-bubbles for 4 minutes, and then pre-deoxidizing with Fe-Si alloy or Fe-Si-Mn alloy in the ladle, adjusting the free oxygen content in the molten steel to 30ppm, stirring with micro-sub-bubbles for 4 minutes, and then final deoxidizing with a composite additive; the composite additive is added to the molten steel in the form of a block alloy or a cored wire, and the particle size of the composite additive is 6mm; the amount of the composite additive added is 0.89kg per ton of molten steel, and then the molten steel is subjected to LF refining and RH refining according to conventional processes.

[0079] Among them, LF refining:

[0080] The viscosity of the refined slag is controlled at 1.513-1.927 Pa·s to improve the ability of the slag system to absorb inclusions, thereby improving the cleanliness of the molten steel; the basicity of the white slag of the refining furnace is controlled at 5.22≤R≤7.43, which is beneficial to improving the desulfurization rate, improving the cleanliness of the molten steel, and reducing oxide inclusions in the molten steel; the MI slag index (=CaO / SiO2:Al2O3 ratio) is controlled at MI>0.153, and the distribution coefficient of sulfur is greatly increased, thereby controlling the appropriate fluidity of the refined slag at a certain basicity; the white slag retention time is ≥14.37min, the refining cycle is ≥39.51min, and the soft blowing time is guaranteed to be>4.63min, thereby controlling the outgoing [O] content.

[0081] Among them, RH vacuum treatment:

[0082] The vacuum chamber pressure is pumped down to below 66.67 kPa and maintained for 12.24-14.36 min. The bottom blowing argon flow rate is 10.17-19.43 m 3 / h to achieve 6 cycles of molten steel; strictly control the type and weight of added alloys, use higher-grade low-carbon ferromanganese, metallic manganese, low-carbon ferrosilicon, ferrotitanium and other alloys to ensure that the molten steel composition is fully qualified, and ensure that the vacuum is maintained for more than 5.31 minutes after the alloy is added to obtain purer molten steel; at the same time, provide a suitable molten steel temperature for continuous casting to ensure that the superheat of the tundish is 10.31-29.25℃ above the liquidus.

[0083] The refined molten steel is then continuously cast according to conventional processes: the temperature of the continuous casting tundish is 1540°C and the casting speed is 1.25 m / s.

[0084] 2) The ingot is subjected to conventional heating and soaking treatment at a temperature of 1187° C. for 3.5 hours to obtain a heat-treated ingot.

[0085] 3) The heat-treated ingot is continuously rolled, and the final rolling temperature is controlled to be 770° C. After rolling, it is cooled to 430° C. by water pouring, and then naturally cooled to room temperature to obtain marine steel.

[0086] In step 3), the rolling method is as follows: heating the ingot at 1210°C for 3.1 hours; continuously rolling the ingot into a product steel plate, and controlling the final rolling temperature to 770°C, cooling the ingot to 430°C after rolling by pouring water; and naturally cooling the ingot to room temperature for standby use.

[0087] The structure type of the offshore steel plate obtained according to the above composition and preparation process is acicular ferrite + polygonal grain boundary ferrite, and the ratio of polygonal grain boundary ferrite to acicular ferrite is 4. The density of corrosion active inclusions in the steel plate is 4.7 / mm 2 The saturation current density of the steel plate at the static electrode potential (Е=-300mV) is 5.5mA. The corrosion rate of the steel plate in simulated seawater solution (3.5% NaCl solution) is ≤0.038 / mm·a.

[0088] Test example

[0089] The corrosion resistance of the marine engineering steel with excellent seawater corrosion resistance prepared in Example 1 is analyzed and tested below.

[0090] 1. Test methods

[0091] (1) Electrochemical corrosion test

[0092] The experimental environment of the electrochemical corrosion experiment is room temperature, and the corrosive liquid is 3.5% NaCl solution to simulate the corrosion environment. The electrode adopts the classic three-electrode system. The sample is the working electrode, the platinum electrode is the auxiliary electrode, and the saturated calomel electrode is the reference electrode (SCE). The electrochemical equipment is a ZAHNER electrochemical workstation, and the parameters are set using Thales electrochemical software. The workstation is connected to a computer for data display.

[0093] The electrochemical corrosion experiment was carried out at room temperature, and the potentiodynamic polarization curve (Tafel) and electrochemical impedance spectroscopy (EIS) of the small sample were tested. Before the test, the sample was immersed in the corrosion solution for 40 minutes, and the electrochemical impedance spectroscopy and potentiodynamic polarization tests were performed after the open circuit potential (OCP) was stabilized. The transition signal of the sinusoidal wave applied by the electrochemical impedance spectroscopy was 10mV, and the test scanning range was 10mHz~10kHz. The scanning rate of the potentiodynamic polarization curve was 0.5mV / s, and the scanning range was -600mV~1.2V. The potentiodynamic polarization curve and electrochemical impedance curve were fitted using origin and Zsimpwin software respectively.

[0094] The AC impedance method disturbs the electrode system with small-amplitude sinusoidal waves of different frequencies. The equivalent circuit of the electrode is inferred through the relationship between the electrode system response and the disturbance signal. The parameters of each component in the equivalent circuit are fitted to obtain the corrosion kinetic parameters of the material. The factors affecting the corrosion resistance of the material can be analyzed intuitively and quantitatively, and the corrosion behavior of the material can be further understood.

[0095] The corrosion electrochemical experiments were all carried out in the classic three-electrode system, with the electrochemical sample to be tested as the working electrode, the saturated calomel electrode (SCE) as the reference electrode, and the platinum sheet as the counter electrode. The test temperature was 25°C. At room temperature, the weld metal was first immersed in the corrosive solution to test the open circuit potential (OCP). The test time was 40 minutes, and the electrochemical impedance test was started after the open circuit potential stabilized. The amplitude of the sine wave applied by the electrochemical AC impedance was 10mV, the scanning frequency range was 10mHz~10kHz, and the scanning time was 40 minutes.

[0096] (2) Determination of the density of corrosion-active inclusions

[0097] The sample was cut into 10×10×10mm, the surface was mechanically ground to 1500 mesh and then polished to a mirror surface, and the corrosion reagent was prepared according to the following proportions: 4.5-5.5mL concentrated hydrochloric acid, 0.08-0.15gCuCl2, 0.03-0.08gSnCl2, and 2.6-3.4gFeCl3 were contained in every 100mL ethanol solution. The corrosion reagent was dropped on the surface of the sample for 5-10s, and then the surface was rinsed with alcohol and dried, and the surface was placed under a metallographic microscope to count the density of corrosion active inclusions at 100× magnification.

[0098] 2. Test results and analysis

[0099] Figure 1 The potentiodynamic polarization results of the offshore steel prepared in Example 1 in 3.5% NaCl solution are shown in FIG. Figure 1 It can be seen that the corrosion potential of the marine steel prepared in Example 1 is -0.535V, and the corrosion current density is: 2.012×10 -5 A.cm -2 .

[0100] Figure 2 To compare the potentiodynamic polarization results of steel in 3.5% NaCl solution. Figure 2 It can be seen that the corrosion potential of the comparison steel is -0.5619V, and the corrosion current density is: 8.509×10 -5 A.cm -2 .

[0101] Figure 3 (ad) are the AC impedance test results of the marine steel prepared in Example 1 in 3.5% NaCl solution. Table 1 is the AC impedance fitting results. The constant phase angle index n in the table reflects the degree of deviation between the actual capacitance and the ideal capacitance. The larger the value of n, the smaller the degree of deviation from the ideal capacitance. Generally, the n value of the double-layer capacitance of the corrosion electrode is between 0.5 and 1. Figure 3 As shown in Table 1, the charge transfer resistance of the marine steel prepared in Example 1 is 808.6 Ω·cm -2 .

[0102] Table 1 shows the AC impedance fitting results of the marine steel prepared in Example 1 in 3.5% NaCl solution

[0103]

[0104] Figure 4 (ad) are the AC impedance test results of the offshore steel prepared in Example 1 in 3.5% NaCl solution. Table 2 is the AC impedance fitting results. Figure 4 As shown in Table 2, the charge transfer resistance of the comparative steel is 233.7Ω·cm -2 .

[0105] Table 2 AC impedance fitting results of comparative steel in 3.5% NaCl solution

[0106]

[0107] Figure 5 The saturation current density of the marine engineering steel prepared in Example 1 obtained by constant potential polarization test is 3.25 mA / cm 2 . It is generally considered that: 6mA / cm 2≤Saturation current density≤8mA / cm 2 It is considered to have good corrosion resistance to chloride ion water medium. Saturation current density ≤ 6mA / cm 2 The above results show that the marine steel of the present invention has excellent corrosion resistance to chloride ion aqueous medium.

[0108] Figure 6 The saturation current density of the comparative steel obtained by constant potential polarization test is 5.71 mA / cm 2 The above results show that the comparative steel has good corrosion resistance to chloride ion aqueous medium.

[0109] Figure 7 This is a micrograph of corrosion active inclusions in the comparison steel. The measurement results show that the density of corrosion active inclusions in the comparison steel is 15 / mm 2 .

[0110] Figure 8 This is a microscopic photo of corrosion active inclusions in the offshore steel prepared in Example 1. The measurement results show that the density of corrosion active inclusions in the offshore steel prepared in Example 1 is 4 / mm 2 The density of corrosion active inclusions in the marine engineering steel prepared in Example 1 is less than 50% of that in the comparative steel.

[0111] It can be seen from the above test results that the order of corrosion current density from large to small is: comparison steel > offshore steel prepared in Example 1, the order of charge transfer resistance from small to large is: comparison steel < offshore steel prepared in Example 1, and the order of saturation current density from large to small is: comparison steel > offshore steel prepared in Example 1, indicating that the offshore steel prepared in Example 1 has excellent resistance to chloride ion aqueous medium corrosion and is significantly better than the comparison steel.

[0112] In summary, the marine steel plate of the present invention adopts a low-carbon, low-silicon, medium-chromium cheap chemical composition design, and does not contain precious corrosion-resistant metal elements such as Ni and Cu, which greatly reduces the material cost; the present invention does not adopt the traditional Al deoxidation technology, but instead uses Si deoxidation, and composite deoxidation supplemented by Zr-RE to form fine, dispersed and uniform composite oxysulfides, which greatly reduces the density of corrosion-active inclusions and significantly improves the seawater corrosion resistance. This type of steel is particularly suitable for marine engineering steel, ship and ship steel, offshore fixed wind power steel, offshore floating wind power steel, coastal cross-sea bridge steel, tower steel, rail steel and other marine environment steel, which can significantly improve the corrosion performance of seawater media rich in chloride ions.

[0113] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0114] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A marine engineering steel resistant to seawater corrosion, characterized in that: It is composed of the following chemical components by mass percentage: C: 0.011 - 0.069%, Si: 0.11 - 0.29%, Cr: 1.51 - 1.99%, Nb: 0.02 - 0.05%, Zr: 0.01 - 0.02%, RE: 0.0034 - 0.02%, and the rest is Fe and inevitable impurities; the mass percentages of Zr element and RE element also simultaneously satisfy the formula: 0.01% < Zr + RE < 0.02% and Zr / RE = 1 - 3.

2. The marine engineering steel resistant to seawater corrosion according to claim 1, characterized in that: It is composed of the following chemical components by mass percentage: C: 0.029 - 0.068%, Si: 0.15 - 0.28%, Cr: 1.55 - 1.78%, Nb: 0.025 - 0.049%, Zr: 0.01 - 0.0117%, RE: 0.0039 - 0.0099%, and the rest is Fe and inevitable impurities.

3. The marine engineering steel resistant to seawater corrosion according to claim 1, characterized in that: It is composed of the following chemical components by mass percentage: C: 0.04%, Si: 0.20%, Cr: 1.75%, Nb: 0.035%, Zr: 0.012%, RE: 0.006%, and the rest is Fe and inevitable impurities.

4. The marine engineering steel resistant to seawater corrosion according to any one of claims 1 to 3, characterized in that: Among the inevitable impurities, the mass percentage of S element satisfies: S ≤ 0.0010%.

5. The marine engineering steel resistant to seawater corrosion according to any one of claims 1 to 3, characterized in that: The RE element described includes lanthanum and cerium, and the weight ratio of lanthanum element to cerium element is (70 - 90):(10 - 30).

6. The marine engineering steel resistant to seawater corrosion according to any one of claims 1 to 3, characterized in that: The microstructure type of the offshore steel is acicular ferrite and polygonal grain boundary ferrite, and the quantity ratio of the polygonal grain boundary ferrite to the acicular ferrite is 4 - 8.

7. The marine engineering steel resistant to seawater corrosion according to any one of claims 1 to 3, characterized in that: The density of corrosion active inclusions in the marine steel is less than or equal to 5 / mm 2 .

8. The marine engineering steel resistant to seawater corrosion according to any one of claims 1 to 3, characterized in that: Under the condition that the static electrode potential is equal to -300 mV, the saturation current density of the offshore steel is less than or equal to 6.0 mA; under the condition that the mass content of NaCl in the seawater solution is 3.5%, the corrosion rate of the offshore steel is less than or equal to 0.04 mm / a.

9. A method for preparing a marine engineering steel resistant to seawater corrosion according to any one of claims 1 to 8, characterized in that: It includes the following steps: 1) Smelt and refine the molten steel in sequence, then conduct vacuum treatment, and finally continuously cast it into a billet to obtain a cast billet; 2) Heat and homogenize the cast billet to obtain a heat-treated cast billet; 3) Continuously roll the heat-treated cast billet, and control the final rolling temperature to be 750 - 850 °C, water-cool it to 410 - 550 °C after rolling, and then naturally cool it to room temperature to obtain offshore steel.

10. The method for preparing a marine engineering steel resistant to seawater corrosion according to claim 9, characterized in that: The smelting and refining methods in step 1) are: using a converter or an electric arc furnace to convert molten iron and / or scrap steel into molten steel after steelmaking, adjusting the temperature and composition, and obtaining molten steel; making the molten steel enter a ladle, and under the stirring of micro-submerged bubbles, pre-deoxidizing the molten steel in the ladle with Fe-Si alloy or Fe-Si-Mn alloy to adjust the free oxygen content in the molten steel to 19 - 99 ppm; under the stirring of micro-submerged bubbles, conducting final deoxidation with a composite additive, and subjecting the finally deoxidized molten steel to LF refining, VD refining, or RH refining.

Citation Information

Patent Citations

  • Corrosion-resistant steel plate for ocean platform and production method of steel plate

    CN110284056A

  • Q690 corrosion-resistant steel for mine environmental service and preparation method thereof

    CN110863147A